2021
DOI: 10.3390/ijerph182312767
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Providers’ Perceptions of Potentially Preventable Rural Hospitalisations: A Qualitative Study

Abstract: Potentially preventable hospitalisations (PPHs) are common in rural communities in Australia and around the world. Healthcare providers have a perspective on PPHs that may not be accessible by analysing routine patient data. This study explores the factors that healthcare providers believe cause PPHs and seeks to identify strategies for preventing them. Physicians, nurses, paramedics, and health administrators with experience in managing rural patients with PPHs were recruited from southern Tasmania, Australia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 48 publications
(91 reference statements)
0
16
0
Order By: Relevance
“…A further 26 papers were excluded for not meeting inclusion criteria, leaving 13 papers for review and analysis ( Figure 1 ). Eight papers were quantitative/descriptive studies [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ] and five were qualitative studies [ 40 , 41 , 42 , 43 , 44 ]. Only one study reported no statistically significant association between the variables studied (physician supply) and rural PPH risk [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A further 26 papers were excluded for not meeting inclusion criteria, leaving 13 papers for review and analysis ( Figure 1 ). Eight papers were quantitative/descriptive studies [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ] and five were qualitative studies [ 40 , 41 , 42 , 43 , 44 ]. Only one study reported no statistically significant association between the variables studied (physician supply) and rural PPH risk [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…The population for study was variably described; this included being conducted in administrative areas serviced by “rural Indian Health Services” [ 34 ] or rural “health professional shortage areas” in Nebraska [ 39 ]. Other studies described a specific rural region of Tasmania [ 36 , 40 , 41 ], Victoria [ 32 ], or New South Wales [ 37 , 42 , 43 , 44 ] as the setting. The remainder used large, usually national, datasets from which rural patient data could be extracted.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, to address PPHs in people with dementia, recent research has focused on assessing effectiveness of interventions by supporting carers to manage the health needs of the person with dementia [ 46 ]. In this context, it is also important to consider health literacy challenges faced by patients and their carers who often do not have a good understanding of where, when and how to manage their health [ 47 ]. At the same time, it is important to understand physicians’ views on PPHs, where previous studies have shown that many physicians hold the views that hospitalisations for ACSCs were unavoidable [ 41 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…If the expectations of the patients’ and medical staff’s quality of the environment is ensured, their comfort and well-being improve. In this area, architecture can play a significant role and predetermine the overall treatment process [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%